The activity of trypsin in the pancreatic juice and blood of poultry increases simultaneously in the postprandial period - Vertiprakhov, Vladimir G.; Ovchinnikova, Natalya V. (Frontiers in Physiology, 2022)
Modern literature data indicate that the role of trypsin goes far beyond its digestive function. Once in the blood, trypsin is involved as part of the kallikrein-kinin system in the regulation of blood pressure, regulates pancreatic function by activating PAR receptors, and influences inflammation and immunity in the cell. The interaction of trypsin in the intestine and serum in the living healthy organism has been insufficiently studied. On the basis of our own studies and literature data, we concluded that after overnight fasting the increase of trypsin activity in pancreatic juice and blood serum in the postprandial period occurs in parallel, which determines not only digestion of food protein but also the level of metabolism. Consequently, determining the optimal amount of crude protein in the diet during the morning meal is a paramount task for physiologists.